Foot model for tracking temperature of safety boot insoles: application to different insole materials in firefighter boots. Issue 1 (2nd January 2016) - García-Hernández, César; Sánchez-Álvarez, Eduardo J.; Huertas-Talón, José-Luis
Abstract : This research is based on the development of a human foot model to study the temperature conditions of a foot bottom surface under extreme external conditions. This foot model is made by combining different manufacturing techniques to enable the simulation of bones and tissues, allowing the placement of sensors on its surface to track the temperature values of different points inside a shoe. These sensors let researchers capture valuable data during a defined period of time, making it possible to compare the features of different safety boots, socks or soles, among others. In this case, it has been applied to compare different plantar insole materials, placed into safety boots on a high-temperature surface.